2018
DOI: 10.1177/2055217318765288
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of mesenchymal stem cell culture expansion for a phase I clinical trial in multiple sclerosis

Abstract: BackgroundMultiple sclerosis is an inflammatory, neurodegenerative disease of the central nervous system for which therapeutic mesenchymal stem cell transplantation is under study. Published experience of culture-expanding multiple sclerosis patients’ mesenchymal stem cells for clinical trials is limited.ObjectiveTo determine the feasibility of culture-expanding multiple sclerosis patients’ mesenchymal stem cells for clinical use.MethodsIn a phase I trial, autologous, bone marrow-derived mesenchymal stem cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 34 publications
0
11
0
Order By: Relevance
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 4 more Smart Citations
“…Stem cell‐based therapies can greatly impact the field of regenerative medicine. MSCs have been used in preclinical and clinical studies to treat degenerative diseases, such as AD (Cui et al, ; Han et al, ; J. Shin et al, ; X. Wang, Ma, et al, ), DDD (Ahn et al, ; Beeravolu et al, ; Pereira et al, ; Perez‐Cruet et al, ), MS (Harris et al, ; Nasri et al, ; Planchon et al, ), PD (Jamali et al, ; H. Kim, Lee, et al, ), and RDD (Mead, Amaral, & Tomarev, ), as summarized in Table . The regenerative mechanisms of transplanted MSCs for these diseases are still unclear; however, some reports have suggested that MSCs have the potential to differentiate or have paracrine effects in vivo (Lee, Choi, Cha, & Hwang, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
“…These dopaminergic neuron cells survived when transplanted into a rat model of PD and displayed greater improvement of behavioral impairments (Y. Wang et al, ). In addition, MSCs have been investigated for the treatment of MS (Harris et al, ; Nasri et al, ; Planchon et al, ). Potential of the MSCs differentiated into neural progenitor cells was investigated to treat MS using a chronic experimental autoimmune encephalomyelitis (EAE) mouse model (Constantinescu, Farooqi, O'Brien, & Gran, ).…”
Section: Promising Applications Of Mscsmentioning
confidence: 99%
See 3 more Smart Citations